Molecular perovskites as a new platform for designing advanced multi-component energetic crystals - Wei-Xiong Zhang; Shao-Li Chen; Yu Shang; Zhi-Hong Yu; Xiao-Ming Chen (Energetic Materials Frontiers, 2020)
Molecular perovskite energetic crystals, as an emerging family of promising practicable energetic materials, have attracted increasing attentions in the past few years. Different from the mainstream strategies focusing on the intra-molecular designs and modifications on fused-ring energetic molecules/ions, molecular perovskites rely on the self-assembly of diverse molecular components into specified ternary crystal structures, hence generally could be prepared via an easy scale-up process at a low cost. As a kind of ternary salts, they have some unique advantages on the energetic-material designs in terms of optimizing oxygen balance, increasing pack efficiency (and crystal density), and decreasing hygroscopicity, hence could achieve improved detonation performances meanwhile overcome some technical weaknesses of traditional energetic binary salts. In this review, we summarize the current findings and understandings on molecular perovskite energetic crystals, and provide an outlook for the new opportunities brought by this new and promising material family towards advanced multi-component energetic crystals.